Effects of paroxetine combined with sulpiride on sleep status and quality of life in patients with depressive episodes - Zhao, Di; Liu, Chunyu (Frontiers in Psychiatry, 2025)
ObjectiveAssess the clinical efficacy of paroxetine and sulpiride IV drip in treating depression and its impact on sleep and quality of life.MethodsRetrospective analysis of 80 depression patients, divided into a study group treated with paroxetine and sulpiride IV drip, and a control group treated with paroxetine alone, over 8 weeks. HAMD and SF-36 assessed depression and quality of life; TESS evaluated adverse reactions.ResultsHAMD scores decreased in both groups, with the study group showing better depression status at 1, 2, and 4 weeks (P<0.05) and higher effective rates (P<0.05). The study group had faster symptom relief. SF-36 scores in role physical, general health, vitality, and role emotional were higher in the study group (P<0.05). TESS scores showed no significant difference between groups (P>0.05), with mild adverse reactions.ConclusionParoxetine with sulpiride IV drip offers rapid relief and high safety in depression treatment, improving sleep and quality of life.